Novel Neonatal Variants of the Carbamoyl Phosphate Synthetase 1 Deficiency: Two Case Reports and Review of Literature - Yan, Beibei; Wang, Chao; Zhang, Kaihui; Zhang, Haiyan; Gao, Min; Lv, Yuqiang; Li, Xiaoying; Liu, Yi; Gai, Zhongtao (Frontiers in Genetics, 2019)
Carbamoyl phosphate synthetase I (CPS1) deficiency (CPS1D), a rare autosomal recessive disorder, characterized by life-threatening hyperammonemia. In this study, we presented detailed clinical manifestations and genetic analysis of two patients with neonatal-onset CPS1D and identified 4 compound heterozygous variants in CPS1 by next generation sequencing. One mutation of c.1631C>T (p.T544M) was known pathogenic, while other 3 variants were novel, including a missense (c.1981G>T, p.G661C), a nonsense (c.2896G>T, p.E966X), and a splicing change of c.622-3C>G, which were predicted to be pathogenic after exhaustive analysis. We reviewed currently available publications regarding CPS1 mutations and totally 264 different variants have been reported with majority of 157 (59.5%) missense, followed by 35 (13.2%) small deletions. The large deletions with missing 1000 bp to 767 kb and small indel accounted for 1.9% and 1.5%, individually. This study expanded the mutational spectrum of CPS1 and our review further support that most (≥90%) of the mutations were “private” and only ~10% recurred in unrelated families.